2013
DOI: 10.1007/s00296-013-2783-3
|View full text |Cite
|
Sign up to set email alerts
|

Organ damage in high-risk patients with systemic and incomplete lupus syndromes

Abstract: The objective of this study was to characterize organ damage in lupus patients enrolled in the Dallas Regional Autoimmune Disease Registry (DRADR). Retrospective chart review was carried out on 99 patients with 4 or more diagnostic criteria for systemic lupus erythematosus (SLE) and 15 with less than 4 of these criteria, who were designated as having incomplete lupus (ILE). The majority of patients (84%) were African American or Hispanic/Latino; mean disease duration was 9.5 years. The mean damage score was 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…In some of these ILE patients, loss of scoring for photosensitivity was counterbalanced by the addition of hypocomplementemia, resulting in no change in the overall score. As in most of the other reports, renal and neurologic criteria were rare or absent in ILE [18] and the more specific antibodies such as dsDNA were also significantly less prevalent than in SLE.…”
Section: Discussionsupporting
confidence: 72%
“…In some of these ILE patients, loss of scoring for photosensitivity was counterbalanced by the addition of hypocomplementemia, resulting in no change in the overall score. As in most of the other reports, renal and neurologic criteria were rare or absent in ILE [18] and the more specific antibodies such as dsDNA were also significantly less prevalent than in SLE.…”
Section: Discussionsupporting
confidence: 72%
“…In this retrospective study cohort, 15 individuals out of 124 were classified as ILE and 99 out of 124 were classified as SLE. (31) The ILE patients were shown to have a significantly lower mean damage score than SLE patients (0.67 ± 0.32 vs 1.67 ± 0.17; p=0.036) and a significantly shorter disease duration (4.33 ± 0.94 years vs 10.24 ± 0.75 years; p=0.003). (31) In another US-based study from the DRADR following 22 ILE Patients (<4 ACR criteria) for an average of 2.4 years, 14% (n=3) transitioned to SLE classification.…”
Section: Introductionmentioning
confidence: 89%
“…(31) The ILE patients were shown to have a significantly lower mean damage score than SLE patients (0.67 ± 0.32 vs 1.67 ± 0.17; p=0.036) and a significantly shorter disease duration (4.33 ± 0.94 years vs 10.24 ± 0.75 years; p=0.003). (31) In another US-based study from the DRADR following 22 ILE Patients (<4 ACR criteria) for an average of 2.4 years, 14% (n=3) transitioned to SLE classification. (32) All patients who transitioned were female, of younger age, and showed increases in IgG autoreactivity.…”
Section: Introductionmentioning
confidence: 96%
“…In most of these studies, only a small proportion of patients (approximately 20%) evolve to either SLE classification or SLE diagnosis 9,10 The term “undifferentiated connective tissue disease” (UCTD) has been used to refer to individuals presenting with clinical symptoms suggestive of some autoimmune connective tissue disease (SLE, Sjögren’s syndrome, scleroderma, mixed connective tissue disease or RA), but not clearly meeting ACR classification criteria for any of these diseases, a common clinical scenario. Follow-up studies of UCTD patients have revealed the rates of progressing to SLE are very similar to those in incomplete lupus cohorts, approximately 20% 919 .…”
mentioning
confidence: 99%
“…Follow-up studies of UCTD patients have revealed the rates of progressing to SLE are very similar to those in incomplete lupus cohorts, approximately 20% 919 . Additionally, those patients who have a prolonged clinical onset of their SLE tend to have a mild disease course, without severe organ involvement 10 .…”
mentioning
confidence: 99%